Islamic Banking Transaction and Social Based Crowdfunding During Pandemic: Shariah Analysis on Islamic Financial and Non-Financial Institutions Approaches - Md. Nor, Mohd Zakhiri; Rachmawati, Irma; Azhar, Alias; Yusof, Yuhanif; Halim, Rohizan; Azrae, Ahmad Nasyran; Wan Ahmad, Wan Izzat; Sumadikara, T. Subarsyah; Turmantar, Firman; Sumantry, Deden; Mulyadi, Leni Wini; Santika, Tisni; et al. (SEK Education Group, 2021)
This paper is based on an ongoing study titled "Social Based - Crowd Funding in Battling Covid - 19 and Maqasid Shariah: Some Legal and Shariah Observations in Malaysia and Indonesia." The COVID-19 pandemic has been one of the most serious health crises since the turn of the century. The corona pandemic has presented Islamic banks with significant challenges in dealing with this pandemic, taking into account, on the one hand, its impact on various economic sectors and regulatory authorities' decisions. However, it appears that Islamic financial institutions are at odds over how to handle Islamic banking transactions, particularly a moratorium between the bank and their clients during the pandemic, as well as the use of social-based crowdfunding activities. This investigation begins with a historical pandemic that afflicted the entire world. The purpose of this paper is to examine the position of Islamic banking transactions and social-based crowdfunding during the pandemic from a Shariah standpoint. This paper also highlights Malaysia's Islamic banking approach to social based financing and social based crowd funding by financial and non-financial institutions during the pandemic. The qualitative research method was used in this paper, which included a library-based research method. A descriptive content analysis method will be used to analyse the data. This paper is significant in that it will add to the body of knowledge and literature on the subject while also providing Shariah's perspective on the status of Shariah's commercial and socially based crowdfunding contracts. The principles of adl and Ihsan appear to have been applied, affecting Islamic banking commercial transactions and social-based crowdfunding contracts. During a pandemic, however, there is a need to strike a balance between the financial stability of the financial institution and the needs of society as a whole. As a result, Shariah parameters must be developed in such a way that financial institutions understand how Islamic commercial transactions and socially based crowdfunding should be treated, particularly during a pandemic